2013
DOI: 10.4103/0971-6866.124376
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 Gene Variant - its Association in Isolated Hypodontia: A Case Control Genetic study!!!

Abstract: INTRODUCTION:Non-syndromic tooth agenesis is a congenital anomaly with significant medical, psychological, and social ramifications. There is sufficient evidence to hypothesize that locus for this condition can be identified by candidate genes.AIM OF THE STUDY:The aim of this study was to test whether MSX1 671 T > C gene variant was involved in etiology of non-syndromic tooth agenesis in Raichur patients.MATERIALS AND METHODS:Blood samples were collected with informed consent from 50 subjects having non-syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…This suggests that since the interval was not short, there may be a more prevalent tendency for hypodontia prevalence in females. We may agree with the results of some surveys, although other studies have documented females prominence over males (31).…”
Section: Prevalence By Type Of Teethsupporting
confidence: 93%
“…This suggests that since the interval was not short, there may be a more prevalent tendency for hypodontia prevalence in females. We may agree with the results of some surveys, although other studies have documented females prominence over males (31).…”
Section: Prevalence By Type Of Teethsupporting
confidence: 93%
“…It was observed that, in addition to developing the agenesis of certain dental groups, mutations of this gene were also related to the occurrence of cleft lip and/or palate (Gene, 2010). Research, Society and Development, v. 9, n. 11, e2449119882, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9882 8 Current mutations reported in the MSX1 Reddy, et at., (2013) aimed to evaluate whether the msx1 671 T> C gene variant was involved in the etiology of non-syndromic dental agenesis in Raichur patients. Blood samples were collected from 50 affected individuals (test group) and 50 patients without agenesis (control group).…”
Section: Msx1mentioning
confidence: 99%